Added effect of 1% topical alendronate in intra-bony and inter-radicular defects as part of step II periodontal therapy: a systematic review with meta-analysis and trial sequential analysis - Claudia Arena; Vito Carlo Alberto Caponio; Khrystyna Zhurakivska; Lucio Lo Russo; Lorenzo Lo Muzio; Giuseppe Troiano (BMC, 2022)
Abstract Background This systematic review and meta-analysis aimed to investigate the role of alendronate combined with step 2 of periodontal therapy in reducing probing pocket depth, improving clinical attachment level, and reducing bone defect depth in intra-bony and inter-radicular defects. Methods RCTs with more than 6 months follow-up were included in this study. Risk of bias assessment was performed using the Cochrane collaboration tool. In addition, meta-analysis and trial sequential analysis were used to aggregate the available evidence. Results Seven studies met the inclusion criteria and were included in the systematic review. Topical application of alendronate during second step of periodontal therapy significantly improved PD and CAL. Conclusion Local application of alendronate may confer a beneficial effect when applied during step II of periodontal therapy even if long term studies are needed to confirm these results. Clinical relevance Considering the emerging role of host-inflammatory response in treatment of periodontitis and the antiresorptive and osteostimulative properties of bisphosphonates, several studies are focusing on the role of alendronate as an addition to non-surgical periodontal therapy.